Optimization of Salt-Leaching Parameters for Gelatin/Na2Ti3O7 Scaffolds Using a Mixture Design Experiment - Rittichai Sangkatip; Wipoo Sriseubsai; Kunlanan Kiatkittipong; Kaona Jongwuttanaruk (My University, 2022)
The purpose of this research was to learn the formation of biomedical scaffold material from gelatin by using titanate (Na2Ti3O7), which is a newly synthesized derivative of titanium dioxide (TiO2) with gelatin. It was prepared by mixed several solutions and cross-linked molecules by heating and salt-leaching. The biomedical scaffold was formed, and its porosity depended on the size of the salt crystal. The mixture was designed by using a mixture design with three factors: gelatin, titanate, and deionized water to determine the optimal mixture for the tensile strength of the biomedical scaffold. The microstructure of the biomedical scaffold was studied using scanning electron microscopy (SEM). The findings revealed that Na2Ti3O7 thoroughly pen-extracted the biomedical scaffold, and the tensile strength of the gelatin/titanate scaffold was higher than the biomedical scaffold, which was formed using pure gelatin. By using the mixture design technique, the 14.73% gelatin, 0.2% Na2Ti3O7, and 85.07% DI water got the highest yield of tensile strength (1508.15 kP). This was an about 4.88% increase in the tensile strength property when compared with using TiO2.
Keywords: Gelatin; Bone Tissue Engineering Materials